Ontogenetic pattern change in amphibians: the case of Salamandra corsica - Wouter Beukema (Acta Herpetologica, 2011)
Ontogenetic, post-metamorphic pattern development is a rarely studied topic in amphibian science. As there are indications that the pattern of Salamandra corsica might expand over time, digital image analyses were applied in order to measure several phenotypical variables which were related to the snout vent length. Results show a significant increase of patches which change to irregular shapes while SVL increases. Digital image analysis is identified as a suitable tool to explore pattern shape and change in general, while the documented pattern development in S. corsica might be one of the first quantified cases of post-metamorphic ontogenetic pattern change in amphibians.